Problems of Islamic Religious Education in the Digital Era - Firman Mansir (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
This article discusses an overview of problems and their solutions in learning Islamic religious education in schools in the digital era. This era has directly or indirectly ushered in many changes in the life of Islamic Religious Education. Especially related to learning Islamic Religious Education in the classroom, one example is the emergence of lectures/online learning/e-learning in the world of Education. The research method used is a qualitative approach to literature studies, therefore in carrying out data analysis through descriptive-analytical content analysis. The digital era can be a challenge for the world of Islamic education to adjust to. Islamic religious education is now faced with new challenges, problems, demands, and needs that have never existed before. So it is necessary to update and innovate the system, governance, curriculum, competence of human resources, facilities and infrastructure, culture, work ethic, and others. Otherwise, Islamic religious education will be further left behind. Therefore, it is necessary to find concrete steps/solutions to be able to apply the term ilmi charitable charity science.